(untitled) (Journal of Medical & Health Sciences Review, 2025)
The examination investigates how nursing practices influence various pain management results. This study demonstrates the pivotal role nurses play in beaching high standards of pain care delivery and pain reduction for patients. Nurses help patients achieve better function and life quality by conducting detailed pain evaluations and providing medications along with implementing pain relieving approaches apart from medication. Patients experience better satisfaction rates and follow treatment plans more closely when nurses make delivering education to patients and allowing them control over their decisions their main nursing focus. Humanized care delivery along with teamwork between various departments and promoting an adequate supply of resources represents nursing practice outcomes. Research needs to evaluate specific nursing methods for pain treatment while exploring factors that help or hinder successful pain control practices. One-quarter of the United States population experiences chronic pain which constitutes a common presenting complaint in outpatient medical clinics across the country. The medical condition creates multiple types of prolonged discomfort that persists longer than 3 to 6 months and develops from injuries as well as diseases and unidentified factors. Chronic pain creates major lifetime quality degradation which causes individuals to suffer from both physical disabilities and emotional breakdowns while forcing them to become socially isolated. The improper treatment of chronic pain leads to opioid addiction problems which raise the death rates and sickness rates among these patients. Healthcare providers need to understand chronic pain because this knowledge forms the basis for developing suitable therapeutic approaches.